Schottky barrier height engineering of ti/n-type silicon diode by means of ion implantation - Doldet Tantraviwat (2018)
© 2018, Walailak University. All rights reserved. Herein, boron implantation technique was employed to engineer the Schottky barrier height (SBH) of Ti/n-type silicon junction (Ti/n-Si). The Ti/n-Si Schottky diodes with boron doses of 4, 5.4 and 6.6×1012cm-2at the energy of 25 keV were fabricated with improved rectification and their effective SBHs increased from 0.49 to 0.95. The tuning of the effective SBH is mainly attributed to the presence of shallow p-layer, which modifies the energy band at Ti/n-Si interface. This work clearly shows that the ability to precisely control the SBH, regardless of the metal work function, would facilitate the implementation of Schottky diode into various semiconductor structures, such as MPS (Merged PiN Schottky) diode, in order to improve performance without major modification on the existing metal line process.